2008
DOI: 10.1016/j.febslet.2008.06.044
|View full text |Cite
|
Sign up to set email alerts
|

A769662, a novel activator of AMP‐activated protein kinase, inhibits non‐proteolytic components of the 26S proteasome by an AMPK‐independent mechanism

Abstract: In this work we present evidence that A769662, a novel activator of AMP-activated protein kinase (AMPK), is able to inhibit the function of the 26S proteasome by an AMPK-independent mechanism. Contrary to the mechanism of action of most proteasome inhibitors, A769662 does not affect the proteolytic activities of the 20S core subunit, defining in this way a novel mechanism of inhibition of 26S proteasome activity. Inhibition of proteasome activity by A769662 is reversible and leads to an arrest of cell cycle pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 23 publications
1
71
0
Order By: Relevance
“…We also showed that the effect on glucose uptake is likely mediated by the PI3-kinase/Akt/TBC1D1/TBC1D4 signaling pathway. Thus, although we do not know the mechanism by which the PI3-kinase is activated by A-769662, our data suggest that A-769662 has off-target effects as previously shown (34). This should be taken into consideration in future studies involving A-769662.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…We also showed that the effect on glucose uptake is likely mediated by the PI3-kinase/Akt/TBC1D1/TBC1D4 signaling pathway. Thus, although we do not know the mechanism by which the PI3-kinase is activated by A-769662, our data suggest that A-769662 has off-target effects as previously shown (34). This should be taken into consideration in future studies involving A-769662.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies that have used this compound to study the effects on metabolism in cells and phosphorylation of AMPK and ACC in skeletal muscle have used lower (1-300 M) concentrations (9,13,14,34,37,38). However, on the basis of the relatively poor bioavailability of A-769662 in skeletal muscle compared with liver (9), and since our experimental model involved incubated intact skeletal muscles rather than primarily in vitro studies like those previously reported (14, 37), we wanted to create as high a concentration gradient across the sarcolemma as possible.…”
Section: Discussionmentioning
confidence: 99%
“…6) A latest paper demonstrated that A-769662 was able to inhibit proteasomal function and lead to an arrest of cell cycle progression in an AMPK-independent mannar in mouse embryonic fibroblast (MEF) cells. 20) Therefore, we couldn't rule out the possibility that A-769662 inhibited MCE via inhibition of proteasome activity in 3T3-L1 cells, which needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK activators may have other targets than AMPK [43,44]. In this respect, a recent study has demonstrated that AICAR and phenformin cause dephosphorylation of Akt and glycogen synthase kinase-3 (GSK-3) independently of their effects on AMPK activity [45].…”
Section: Page 18 Of 38mentioning
confidence: 99%